No to Third Term! Pastoral Statement by the Church in Zimbabwe as an Indictment on President Mnangagwa’s Bid to Amend the Constitution - James Ndlovu; Tigere Paidamoyo Muringa (Religions)
The Second Republic of Zimbabwe has witnessed continued political and socio-economic crises. Despite the worsening crisis under the new dispensation, there have been calls for extending the current administration’s term limit beyond 2028. The impending crisis has attracted several responses and criticisms across various sectors. The church collective in Zimbabwe has raised concerns over the crisis and issued several statements commenting on the developments in the national landscape. However, the church has been criticised for failing to speak with one voice, especially on political matters. The purpose of this article is to analyse the ecumenical statement that was released by the Zimbabwe Heads of Christian Denominations (ZHOCD) on 21 January 2025, titled ‘Statement on Presidential Constitutional Term Limit’. The letter is the church leader’s response to the ongoing pronouncements for extending the presidential term limits to allow the incumbent President Emmerson Mnangagwa to rule beyond his constitutionally mandated two terms, into 2030. The paper seeks to establish the role of the prophetic voice of the church in defending the constitution and the implications of such actions on the nature of the church–state relations in the Second Republic of Zimbabwe. The paper draws data from the issued ecumenical statement, the official government response to it, and general responses to it available online.